Evaluation of Esperanza Seaweeds Culture-Enterprise Federation: A Livelihood Project in Masbate, Philippines - Alvin Mahawan; Roger Ibañez Jr; Jacob Frederick Velza (Camarines Sur Polytechnic Colleges, 2022)
The Seaweeds Culture is one of the livelihood initiatives extended by the FishCORAL Project funded by the United Nations-International Fund for Agricultural Development (UN-IFAD) with the Bureau of Fisheries and Aquatic Resources (BFAR) to the fishing households in Barangay Rizal and Libertad, Esperanza, Masbate, Philippines. The study aimed to analyze the socioeconomic characteristics of household beneficiaries, identify the different types of livelihood assets, and evaluate the livelihood key performance of Esperanza Seaweeds Culture-Enterprise Federation. The study included the twenty-one beneficiaries, and data were treated based on cross-sectional quantitative data were gathered through focus group discussion and key informant interviews. It was found out that the household beneficiaries are mostly potential members of the labor force. The household income is insufficient, which translates to high poverty incidence. The income and expenditure approach as PSA's measure of poverty confirmed this. The primary livelihood assets are consumer durables, enterprise federation, credits as significant financial capital, and government transfers associated with buffering mechanisms to sustain the family needs. There is relevance and initial impact, which results in improved livelihood and some improvement in women empowerment. The claimed improvement in income could not be associated with project impact as the culture has just started. There are key challenges to the efficiency and sustainability of the project, especially from the end view of natural and anthropogenic disturbances. These significant risks are appropriately counteracted when the association does have a sustainability plan. The adaptive capacity of the association must be enhanced. Along these ends, the technical backstopping of BFAR, academe, and other agencies are very vital.